Pemilihan Kepala Daerah Oleh Dewan Perwakilan Rakyat Daerah Ditinjau Dari Fiqh Siyasah - Annisa Mayang Tyaningrum (Tasfiyah : Journal of Islamic Law and Sharia Economics, 2026)
The discourse on restoring the mechanism of regional head elections through the Regional People’s Representative Council (DPRD) has generated significant constitutional and democratic debate in Indonesia. While proponents argue that indirect elections may reduce political costs and minimize electoral conflicts, opponents contend that such a system risks weakening public participation and democratic accountability. In this context, the election of regional heads through the DPRD raises important questions regarding its compatibility with democratic principles and the values of fiqh siyasah within the Indonesian constitutional framework. The purpose of writing this article is to analyze the practice of electing regional heads by the Regional People's Representative Council (DPRD) in the perspective of Siyasah Dusturiyah, which is a branch of Islamic political science related to governance based on Islamic law.  This research uses a normative method with a literature and legislation approach that includes positive legal analysis, democratic principles, and the concept of Siyasah Dusturiyah. The results of this study indicate that the election of regional heads by the Regional People’s Representative Council (DPRD) possesses constitutional legitimacy within Indonesia’s positive legal system, as reflected in Article 18 paragraph (4) of the 1945 Constitution, which allows regional heads to be elected democratically through either direct or representative mechanisms. From the perspective of fiqh siyasah, the DPRD-based election system may be considered permissible insofar as it upholds the principles of deliberation (shura), justice (‘adl), public welfare (maslahah), and accountability in governance. Accordingly, the legitimacy of this mechanism depends not merely on its procedural form, but on the extent to which the election process reflects the aspirations and interests of the people in accordance with the values of Islamic governance. This article recommends strengthening transparency and accountability in the election process, as well as optimizing the role of the DPRD as the people's representative to ensure that the election of regional heads is truly oriented towards the interests of the wider community.